A arquitetura iconográfica dos altares dos terreiros de umbanda em Caucaia e Fortaleza no Ceará: uma prática arte-educadora multicultural - Araújo, Sheilla Sousa (2015)
This research aims to study the Umbanda altars of Caucaia and Fortaleza as part of the didactic transposition into art schools, using the photographic record. Realized a record of 17 altars, work settings, and theoretical parts; on which develop the analyzes; completing with the didactic proposal for the teaching of art. I am inserted into the methodological approach of Africanity and afrodescendência therefore start with the memorial of my life story and inserting the theme of Umbanda, its symbols and practices as Brazilian african religion; For artistic knowledge, for didactic treatment (methods for teaching of Brazilian black arts) and for own evaluation systems, as defined and contemplated will from the Law 10.639 / 03. This aims to support teachers and schools in developing and educating learning in a new multicultural design for the teaching of arts education discipline in an interdisciplinary concept.